L2 vocabulary acquisition: the impact of negotiated interaction - Ng, Lee Luan; Sheila Marina Sappathy (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Interaction between teachers and students during teaching/learning sessions and the language during these interactions form the main source of language input besides instructional materials from textbooks and workbooks. Research has shown that appropriate input and suitable contexts for interaction among students can lead to successful second language acquisition (SLA). This study examines the relationship between negotiated interaction and the ability to retain vocabulary items among a group of primary school English as a Second Language (ESL) learners with similar first language (L1) backgrounds. 48 participants took part in a one-way input task which involved traditional teaching/learning methods where the teacher used translations and pictures to teach vocabulary. 24 of the 48 participants took part in an additional two-way interactive task in the form of an information gap task. Learners worked in pairs to describe target vocabulary items in pictures. The interactive sessions were audio/video taped and transcribed. All the 48 participants sat for a pretest and three posttests (both immediate and delayed). The results showed that learners who negotiated for meaning in the two-way task achieved higher vocabulary test scores. The 24 students involved in the interactive task demonstrated their ability to negotiate for meaning despite their lack of proficiency in the language. As negotiated interaction has proved successful in enabling students to acquire and retain vocabulary items, such interactive tasks should be encouraged in the classroom.